A novel endo‐β‐N‐acetylglucosaminidase releases specific N‐glycans depending on different reaction conditions. (4th July 2015) - Parc, Annabelle Le; Karav, Sercan; Bell, Juliana Maria Leite Nobrega De Moura; Frese, Steven A.; Liu, Yan; Mills, David A.; Block, David E.; Barile, Daniela
<x xml:space="preserve">Abstract</x> Milk glycoproteins are involved in different functions and contribute to different cellular processes, including adhesion and signaling, and shape the development of the infant microbiome. Methods have been developed to study the complexities of milk protein glycosylation and understand the role of N‐glycans in protein functionality. Endo‐β‐N‐acetylglucosaminidase (EndoBI‐1) isolated from Bifidobacterium longum subsp. infantis ATCC 15697 is a recently isolated heat‐stable enzyme that cleaves the N‐N′‐diacetyl chitobiose moiety found in the N‐glycan core. The effects of different processing conditions (pH, temperature, reaction time, and enzyme/protein ratio) were evaluated for their ability to change EndoBI‐1 activity on bovine colostrum whey glycoproteins using advanced mass spectrometry. This study shows that EndoBI‐1 is able to cleave a high diversity of N‐glycan structures. Nano‐LC‐Chip–Q‐TOF MS data also revealed that different reaction conditions resulted in different N‐glycan compositions released, thus modifying the relative abundance of N‐glycan types. In general, more sialylated N‐glycans were released at lower temperatures and pH values. These results demonstrated that EndoBI‐1 is able to release a wide variety of N‐glycans, whose compositions can be selectively manipulated using different processing conditions. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1323–1330, 2015